Art in doubt : Tolstoy, Nabokov, and the problem of other minds - Gershkovich, Tatyana (Studies in Russian literature and theory., 2023)
"Leo Tolstoy's and Vladimir Nabokov's radically opposed aesthetic worldviews emanate from a shared intuition-that approaching a text skeptically is easy, but trusting it is hard Two figures central to the Russian literary tradition-Tolstoy, the moralist, and Nabokov, the aesthete-seem to have sharply conflicting ideas about the purpose of literature. Tatyana Gershkovich undermines this familiar opposition by identifying a shared fear at the root of their seemingly antithetical aesthetics: that one's experience of the world might be entirely one's own, private and impossible to share through art. Art in Doubt: Tolstoy, Nabokov, and the Problem of Other Minds reconceives the pair's celebrated fiction and contentious theorizing as coherent, lifelong efforts to reckon with the problem of other people's minds. Gershkovich demonstrates how the authors' shared yearning for an impossibly intimate knowledge of others formed and deformed their fiction and brought them through parallel logic to their rival late styles: Tolstoy's rustic simplicity and Nabokov's baroque complexity. Unlike those authors for whom the skeptical predicament ends in absurdity or despair, Tolstoy and Nabokov both hold out hope that skepticism can be overcome, not by force of will but with the right kind of text, one designed to withstand our impulse to doubt it. Through close readings of key canonical works-Anna Karenina, The Kreutzer Sonata, Hadji Murat, The Gift, Pale Fire-this book brings the twin titans of Russian fiction to bear on contemporary debates about how we read now, and how we ought to"--